Association of Meat Subtypes With Colorectal Polyp Prevalence: Finding From the Lanxi Pre-colorectal Cancer Cohort in China - Chai, Xiaoyin; Li, Yin; Yin, Zihan; Wu, Fei; Hu, Peiling; Liu, Xiaohui; Tong, Shuhan; Zhuang, Pan; Zhang, Yu; Zheng, Weifang; Jiao, Jingjing (Frontiers in Nutrition, 2022)
Background: Although the detrimental effect of red meat on colorectal cancer (CRC) incidence has been extensively reported, no previous studies have comprehensively linked different meat subtypes with colorectal polyp occurrence. The aim was to assess the correlation of meat and subtypes with colorectal polyp prevalence for the high-risk CRC Chinese population. Besides, we also focused on the association according to sizes, subsites, and multiplicity of polyps. Methods: High-risk CRC patients aged 40-80 y were enrolled into the Lanxi Pre-Colorectal Cancer Cohort (LP3C) between March 2018 and December 2019. Cross-sectional analyses were conducted by using the baseline data from LP3C. A validated food frequency questionnaire (FFQ) was employed to collect dietary information. Odds ratios (ORs) and 95% confidence intervals (95% CIs) of colorectal polyp prevalence were estimated by multivariate logistic regression. Results: 2064 colorectal polyp cases were identified among 6783 eligible participants in the survey of LP3C (March 2018 and December 2019). Total meat intake was positively related to rectum polyp prevalence (P for trend =0.01) but was not linked to total colorectal polyps after adjustment for multivariable. For meat subtypes, higher poultry consumption was significantly related to a higher polyp prevalence [OR Q4 vs Q1 (95% CI): 1.20 (1.02-1.42); P for trend =0.03 ]. Processed red meat intake was linked to an increased small polyp prevalence(P for trend =0.03) while unprocessed red meat had a relation with a higher rectum polyp prevalence (P for trend =0.04). Furthermore, seafood intake had a significant association with a higher multiple polyp prevalence [OR Q4 vs Q1 (95% CI): 1.70 (1.31-2.21); P for trend <0.001]. Conclusions: The finding was that poultry meat consumption was related to a higher polyp prevalence. Besides, total meat consumption, processed and unprocessed red meat consumption, seafood consumption had a positive relation with certain polyp subtypes prevalence. Generally recommending reducing total meat consumption, including poultry, processed and unprocessed red meat, seafood intake, may prevent colorectal polyps.